Juridical Review of the Offense of Premeditated Murder - Badaru, Baharuddin (Jurnal Independent, 2023)
AbstractThis study examines the application of the judges' decision in the case in accordance with material and formal criminal law and the judge's efforts in deciding a case of premeditated murder. This research is empirical research, a legal research method that functions to see the law in a real sense and examines how the law works in society. Types of data include primary data and secondary data, using field data collection techniques and literature. The results of the study indicate that the application of material and formal criminal law to premeditated murder cases, the application of criminal provisions in this case, namely Article 340 of the Criminal Code in conjunction with Article 55 Paragraph (1) to 1 of the Criminal Code is in accordance with the legal facts, both the statements of witnesses, the defendant's statement is considered physically and mentally healthy, there is no mental disorder so that they are considered capable of being responsible for their actions. The judge's consideration in imposing criminal sanctions against the perpetrators in the decision Number: 775/Pid.B/2018/PN Mks was appropriate, namely by the fulfillment of all the elements of the articles in the indictment, as well as the witness statements which compatible with each other and supported by the judge's conviction. The recommendation of this research is that the judge should really consider the facts revealed in the Court and also the judge's conscience, not only considering things that are aggravating but also things that relieve the defendant so that the verdict handed down really gives justice to the defendant .